How the Disruption of Mitochondrial Redox Signalling Contributes to Ageing - Beatriz Castejon-Vega; Mario D. Cordero; Alberto Sanz (MDPI AG, 2023)
In the past, mitochondrial reactive oxygen species (mtROS) were considered a byproduct of cellular metabolism. Due to the capacity of mtROS to cause oxidative damage, they were proposed as the main drivers of ageing and age-related diseases. Today, we know that mtROS are cellular messengers instrumental in maintaining cellular homeostasis. As cellular messengers, they are produced in specific places at specific times, and the intensity and duration of the ROS signal determine the downstream effects of mitochondrial redox signalling. We do not know yet all the processes for which mtROS are important, but we have learnt that they are essential in decisions that affect cellular differentiation, proliferation and survival. On top of causing damage due to their capacity to oxidize cellular components, mtROS contribute to the onset of degenerative diseases when redox signalling becomes dysregulated. Here, we review the best-characterized signalling pathways in which mtROS participate and those pathological processes in which they are involved. We focus on how mtROS signalling is altered during ageing and discuss whether the accumulation of damaged mitochondria without signalling capacity is a cause or a consequence of ageing.